Unchanged surface morphology in debris-covered glaciers and rock glaciers in Tröllaskagi peninsula (northern Iceland) - Tanarro García, Luis Miguel; Palacios Estremera, David; De Andrés de Pablo, Nuria; Fernández Fernández, José María; Zamorano, José Juan; Sæmundsson, Þorsteinn; Brynjólfsson, Skafti (Science of The Total Environment, 2019)
This paper analyses changes in the surface morphology of rock and debris-covered glaciers in the Hóladalsjökull and Fremri-Grjótárdalur cirques near Hólar village in the Tröllaskagi peninsula (northern Iceland) (65°43′55″N; 19°06′49″W, 160 m), to understand the dynamics and climatic significance of these landforms. The study includes an analysis of historical aerial photographs from 1946 to 2000. The aim was to evaluate surface changes in these landforms and obtain the horizontal displacement and elevation changes of large boulders and linear features (ridges and furrows) at each date. In addition, the surface elevation differences between 1980 and 1994 were obtained from digital elevation models. The horizontal displacement results obtain a mean velocity of 0.33 m yr−1 and an average elevation difference of −0.72 m for the boulders, with the linear features advancing 14.84 m during the period 1946–2000. Except for this slow mobility, no changes occurred in the surface morphology of these landforms during the 54 years. The low displacement rates of boulders and linear features, together with the surface lowering processes observed in these landforms, indicate that widespread melting is the most important activity in the debris-covered and rock glaciers in Tröllaskagi. This is confirmed by the recent formation of collapse depressions. Ministerio de Economía y Competitividad (España) Nils Mobility Program Depto. de Geografía Fac. de Geografía e Historia TRUE pub